(untitled) - Wyatt, Tristram D. (Cambridge, UK, 2002)
We are entering one of the most exciting periods in the study of chemical communication since the first pheromones were identified some 40 years ago. This rapid progress is reflected in this book, the first to cover the whole animal kingdom at this level for 25 years. The importance of chemical communication is illustrated with examples from a diverse range of animals including humans, marine copepods, Drosophila, Caenorhabditis elegans, moths, snakes, goldfish, elephants and mice. It is designed to be advanced and up-to-date, but at the same time accessible to readers whatever their scientific background. For students of ecology, evolution and behaviour, this book gives an introduction to the rapid progress in our understanding of olfaction at the molecular and neurological level. In addition, it offers chemists, molecular and neurobiologists an insight into the ecological, evolutionary and behavioural context of olfactory communication.
Hóa học sinh thái,Hoá học Sinh thái
Keywords: Animal communication,Pheromones,Chemical senses